Flattening the medieval Earth - Felipe, Pablo de, author.
1 online resource (296 pages)
Keywords: Flattening the Medieval Earth explores the origin of the 'flat error', i.e. the false accusation that ancient and medieval Christians believed in a flat Earth, and what this implies in terms of a conflict between science and Christianity. Engaging with scientific and religious debates, this book includes a reception study of two key figures of the 4th century AD, Lactantius and Augustine. This study demonstrates that the mistaken 'dark' image of medieval scholars as flat-earthers started very early, c. 1600, as an internal Christian debate in the context of new geographical and astronomical views. The author draws on extensive research including many primary and secondary sources from different countries and languages not previously put into conversation. Combining history of science, church history, science and religion, history of navigation, and historiography, this book gives the most updated explanation of the origin of the flat error, finding paradoxes and unexpected answers along the way to understand the past and to reflect on some current approaches in science and religion.